Pelas bordas: reflexões situadas nas fronteiras da produção do conhecimento em PPEL em um período de pós-megaeventos esportivos no Brasil - Leandro Forell; Fabiana Gazzotti Mayboroda (Universidade Estadual do Oeste do Paraná, 2017)
The central idea of this text is to reflect on the construction of the field of Sports and Leisure Public Policy (PPEL). Throughout the text, he seeks to compare the construction of the field with others, such as anthropology. Understanding that there is always a degree of normativity in defining what is inside and outside a given identity, makes a description about some classifications of the field, proposing an analysis of the production from the research objects. It deals with issues related to the analysis of public policies beyond the analysis of the State, including the relationship of this with society as an important object for the field. Advocating in favor of a hybrid understanding, where several disciplines constitute it and that has an interdisciplinary character.